Short communicationIntervention on the left main coronary artery. Importance of periprocedural and follow-up intravascular ultrasonography guidance - Tyczyński, Paweł; Chmielak, Zbigniew; Pręgowski, Jerzy; Rewicki, Marek; Karcz, Maciej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Periprocedural intravascular ultrasonography guidance for left main coronary artery stenting is well established. However, the role of this tool is also important at follow-up interventions. We present a case of a patient with previous history of left main coronary artery angioplasty. During a recent attempt to treat tight stenosis in the left anterior descending coronary artery, it was not possible to advance the stent into the left main coronary artery. Intravascular ultrasonography explained the difficulties encountered.